Long COVID-19: A Primer for Cardiovascular Health Professionals, on Behalf of the CCS Rapid Response Team - Paterson, Ian; Ramanathan, Krishnan; Aurora, Rakesh; Bewick, David; Chow, Chi-Ming; Clarke, Brian; Cowan, Simone; Ducharme, Anique; Gin, Kenneth; Graham, Michelle; Gupta, Anil; Jassal, Davinder S.; et al. (Canadian journal of cardiology, 2021)
It is now widely recognized that COVID-19 illness can be associated with significant intermediate and potentially longer-term physical limitations. The term, “long COVID-19” is used to define any patient with persistent symptoms after acute COVID-19 infection (ie, after 4 weeks). It is postulated that cardiac injury might be linked to symptoms that persist after resolution of acute infection, as part of this syndrome. The Canadian Cardiovascular Society Rapid Response Team has generated this document to provide guidance to health care providers on the optimal management of patients with suspected cardiac complications of long COVID-19. Il est désormais largement reconnu que la COVID-19 peut être associée à d'importantes limitations physiques à moyen terme et, potentiellement, à plus long terme. Le terme « COVID-19 longue » est utilisé pour décrire tout patient présentant des symptômes persistants après une infection aiguë par le virus de la COVID-19 (soit au-delà de quatre semaines). On suppose qu'une atteinte cardiaque pourrait être liée aux symptômes qui persistent après la disparition de l'infection aiguë, dans le cadre de ce syndrome. Le Groupe de travail sur la réaction rapide à la COVID-19 de la Société canadienne de cardiologie a produit le présent document afin de fournir des conseils aux professionnels de la santé sur la prise en charge optimale des patients chez qui l'on soupçonne des complications cardiaques causées par la COVID-19 longue.